Thoroughly revised and updated Engineering Mathematics:for GATE 2019 and ESE 2019 prelims - MADE EASY (MADE EASY PUB, 2018)
Thoroughly revised and updated Engineering Mathematics:for GATE 2019 and ESE 2019 prelims / MADE EASY. -- New Delhi: MADE EASY PUB., 2018 153.9451 M181e10 10th ed No. of Copies : 2